2013
DOI: 10.1002/tox.21905
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity risk assessment of diversely substituted quinolines using the SOS chromotest

Abstract: Quinolines are aromatic nitrogen compounds with wide therapeutic potential to treat parasitic and microbial diseases. In this study, the genotoxicity of quinoline, 4-methylquinoline, 4-nitroquinoline-1-oxide (4-NQO), and diversely functionalized quinoline derivatives and the influence of the substituents (functional groups and/or atoms) on their genotoxicity were tested using the SOS chromotest. Quinoline derivatives that induce genotoxicity by the formation of an enamine epoxide structure did not induce the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Identification of mammalian metabolites of quinoline 1 and their role in its mutagenicity and tumorigenicity, has been of interest for more than 40 years (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Several quinoline arene oxides, e.g., 20 and 27, were initially postulated as possible liver microsomal metabolites of quinoline 1 (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983), before 5,6-arene oxide 20 was finally confirmed as a major metabolite (Figure 8) (Agarwal et al, 1986).…”
Section: Chemoenzymatic Synthesis Of Isolated and Potential Arene Oxide Metabolites Of Quinolinementioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mammalian metabolites of quinoline 1 and their role in its mutagenicity and tumorigenicity, has been of interest for more than 40 years (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Several quinoline arene oxides, e.g., 20 and 27, were initially postulated as possible liver microsomal metabolites of quinoline 1 (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983), before 5,6-arene oxide 20 was finally confirmed as a major metabolite (Figure 8) (Agarwal et al, 1986).…”
Section: Chemoenzymatic Synthesis Of Isolated and Potential Arene Oxide Metabolites Of Quinolinementioning
confidence: 99%
“…Quinoline 1 is a mammalian hepatocarcinogen and a bacterial mutagen, with its metabolites binding covalently to DNA. Possible pathways responsible for these biological effects continue to be of interest (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Cytochrome P-450 (CYP-450) monooxygenases have been identified as responsible for catalyzing epoxidation and dearomatization of quinolines, during mammalian liver metabolism.…”
Section: Introductionmentioning
confidence: 99%